Optimism, Quality of Life, and Psychological Distress in Patients with Type 2 Diabetes Mellitus: A Case–Control Study - Ottilingam S. Ravindran; Natarajan Shanmugasundaram; Saidivya Madhusudhan (Indian Journal of Psychiatric Nursing)
Background: Type 2 diabetes mellitus (T2DM) is a serious chronic illness which has a major impact on the psychological well-being of the individuals. Aim: This case–control study compared the optimism, quality of life (QOL), and psychological distress between T2DM persons and healthy controls and examined the relationship of optimism with QOL and psychological distress among T2DM persons. Materials and Methods: Using a purposive sampling technique, this study was conducted in the General Medicine Outpatient department of a tertiary care hospital between January and March 2020. Fifty participants (25 cases and 25 healthy controls) in the age range of 30–60 years took part in the study. Both groups were assessed by the following instruments: Life Orientation Test-Revised, WHOQOL-BREF, and Depression Anxiety and Stress Scale. Results: T2DM persons are experiencing significant psychological distress with a pessimistic disposition and reduced QOL. Furthermore, optimism was positively correlated with psychological health among T2DM persons. Conclusions: T2DM persons are found to be pessimistic and distressed with significant reductions in their QOL.